HISTOPATHOLOGY CHANGES IN FRESH WATER FISH CLARIAS BATRACHUS(Linn.) EXPOSED TO MERCURY AND CADMIUM: Life Science-Biotechnology - J. SELVANATHAN; S.VINCENT; A. NIRMALA (International Journal of Life Science and Pharma Research, 2013)
The release of heavy metals into the aquatic environment causes water pollution problems because of their toxicity, persistence and bio-accumulation .An investigation on the effect of heavy metals like Mercury and Cadmium on Fresh water fish Clarias batrachus carried out in the lab. Fishes weighing 10 ± 0.5 g and 10 ± 1 cm length were exposed to sublethal concentrations (derived, based on acute toxicity tests) of mercury 0.19, 0.09, 0.05 and 0.03 ppm and of cadmium chloride 0.66, 0.30, 0.17 and 0.12 ppm for 30 days. During this period fishes were fed with artificially prepared food. On the 10th, 20th, 30th day fishes were taken out, sacrificed and the tissues of gill and liver were excised out. The total autopsy was completed in less than 4 mins. The result showed that the degree of distortion of the gill, liver was proportional to the exposure period and concentration of the metals was found to be dose and time dependent.